The Role of Influencer’s Characteristic, E-Wom, and Brand on Purchase Intention in Indonesia’s Japanese Restaurant Industry - Salim, Nicko Christian; Berlianto, Margaretha Pink; Sobirov, Bobur (Yayasan Riset dan Pengembangan Intelektual, 2025)
The increasing use of influencers in digital marketing strategies encourages the importance of understanding the factors that shape satisfaction with influencers and their impact on consumer purchase intentions. This study aims to analyze the effect of attractiveness, trustworthiness, expertise, electronic word of mouth (E-WOM), brand trust, and brand image on purchase intention, with influencer satisfaction as a mediating variable. This research method uses a quantitative approach with data collection techniques through a questionnaire survey to 200 Bobby Saputra followers with a convenience sampling technique. Data analysis was carried out using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results showed that attractiveness, expertise, brand trust, and brand image have a positive effect on influencer satisfaction, where visual appeal, expertise, and perception and trust in the brand are key factors in shaping satisfaction with influencers. Conversely, trustworthiness and E-WOM did not show a significant effect on influencer satisfaction, indicating that personal trust and digital communication are not enough to create satisfaction directly. In relation to purchase intention, it was found that attractiveness, E-WOM, brand trust, brand image, and influencer satisfaction have a positive and significant effect, which confirms the importance of visual aspects, brand reputation, and positive experiences with influencers in driving purchase intention. Meanwhile, trustworthiness and expertise do not have a significant effect on purchase intention, indicating that emotional considerations and brand perceptions are more dominant than personal credibility or technical competence.